Investigations of thermo-ionic emitters of heavy alkali metals for diagnostic injector of “Uragan-2M” stellarator - Bondarenko, I.S.; Chmyga, A.A.; Deshko, G.N.; Komarov, A.D.; Kozachok, A.S.; Krupnik, L.I.; Khrebtov, S.M.; Taschev, Yu.I.; Zhezhera, A.I. (Вопросы атомной науки и техники, 2011)
The results of solid-state thermo-ionic emitters of Cs⁺ and Tl⁺ ions investigations are presented. These emitters are planned to use in heavy ion beam diagnostic system for “Uragan-2M” stellarator. According to estimations for HIBP diagnostic system operations it is necessary to have primary beam current up to 0.5 mA. The aim of these investigations was determination of emission rate, mass-spectrum of ion beam during the beam extraction time and heavy ion beam current stability in area of 0.5 mA.